Pengaruh Contrasbath Therapy dan Rheumatic Exercise Terhadap Perubahan Nyeri dan Rentang Gerak pada Lansia Penderita Osteoarthritis - Agustina Sisilia Wati Dua Wida; Fransiska Aloysia Mukin; Melkias Dikson (Peneliti.net, 2021)
Background: Osteoarthritis (OA) is a chronic and progressive joint disorder that is usually found in middle to old age, which is characterized by damage to cartilages located in the joints of the bones. Its presence is often followed by muscle weakness, limitation in movement and local pain—ultimately decreases the quality of life for patients suffering from it. Purpose: This study aims to analyse the effect of contrast bath therapy and rheumatic exercise on changes of pain and movement range in older people with osteoarthritis. Methods: This research used a quantitative method, i.e., Quasi-Experiment with One Group Pretest-Posttest Design. Based on the design, intervention was only conductedtowards one group without comparison. The effectiveness of the treatment was assessed by comparing the scores pre-test and post-test of 35 elderly respondents, whose inclusion criteria were: elderly residents of the Padu Wau Waipare Social Care Center, Kangae District, Sikka Regency; age> 60 years; having a medical history of knee osteoarthritis and complaints of joint pain (scale 1-9);and not currently experiencing inflammation with uncontrolled severe joint pain scale (scale 10) whichrequires elderlies to have bedrest then analysed using wilcoxon test statistical. Results : The result of Wilcoxon test statistical test indicates that there is an effect of rheumatic exercise and contrast bath therapy on changes in pain levels and range of motion before and after rheumatic exercise therapy in which from the total of 35 respondents who were observed, the z value = -3.357b<z table value and p value = 0.001 (p <0.05). Conclusion: that there is a significant effect caused by rheumatic exercise and contrast bath therapy on changes in pain levels and range of motion. Keywords: Contrast Bath Therapy,Rheumatic Exercise, Pain, Range of Motion, Osteoarthritis, Elderly